Community structure and distribution of culturable bacteria in soil along an altitudinal gradient of Tianshan Mountains, China. Issue 2 (4th March 2018) - Zhao, Yanting; Song, Chunli; Dong, Hongqiang; Luo, Yang; Wei, Yali; Gao, Jiangli; Wu, Qianqian; Huang, Yaolong; An, Lizhe; Sheng, Hongmei
ABSTRACT: The Tianshan Mountains hold important and complex ecosystems. They host some unique biological resources, especially some microbes that have very crucial application values. In this study, the composition and distribution of bacterial communities from soil at different elevations of the Tianshan Mountains, China, were investigated using culture-based and molecular-based methods. The relationship between the abundance of culturable bacteria and environmental factors was also analysed. A total of 121 isolates showing different phenotypic characteristics were obtained from soil and identified by 16S rRNA gene sequencing analysis. All strains were assigned to four phyla: Proteobacteria, Actinobacteria, Bacteroidetes and Firmicutes. Actinobacteria and Proteobacteria were the dominating bacterial phyla; Arthrobacter, Pseudomonas and Sphingomonas were the most prevalent genera. The community structures of culturable bacteria were significantly different at different elevations, there being some common bacterial communities and some unique groups at each altitude. The principal component analysis (PCA) showed that the abundance of culturable bacterial communities has a significant positive correlation with the NO3 − content in the soil. It indicated that NO3 − was a better predictor of soil culturable bacterial abundance in this region. The strains isolated from alpine soil in this study are not only an invaluable part of microbial diversity, but also good candidates for further elucidating the interaction relationship between plants and microorganisms.